PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV DI UPTD SD NEGERI LABUHAN RATU TIGA: Penelitian Tindikan Kelas - Lusi Ratnasari; Bambang Ariyanto; Sulis Anjarwati (STKIP Subang, 2026)
This research was motivated by the low IPAS learning outcomes of fourth-grade students at UPTD SD Negeri Labuhan Ratu Tiga, caused by the lack of variation in learning methods and the suboptimal level of active student involvement. This study aims to improve learning outcomes in the IPAS topic